Peningkatan Keterampilan Passing Bawah Bola Voli Dengan Pendekatan Permainan - Wahyuni, Tri; Hardika, Nevi (Journal Sport Academy, 2022)
The purpose of this study was to describe empirically about "improving volleyball underhand passing skills with a game approach in class V B students of 18 Delta Pawan Elementary School, Ketapang Regency". The method used by researchers is Class Action Research (classroom action research). While the type of research used is collaborative form. The data collection techniques used in this study were direct observation techniques, measurement techniques and data collection tools that were in accordance with this study, namely observation guidelines. The subjects in this study were students in class V B 18 Delta Pawan Elementary School, Ketapang Regency, totaling 21 students. The data analysis used in this study is descriptive qualitative based on the results of observations. The results of this study showed a significant increase through the game approach, so that the results from the pre-cycle to the last cycle showed good changes.